Fixed point theorems for generalized contraction mappings on b-rectangular metric spaces - ALECSA, Cristian Daniel (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In the present article, we study some fixed point theorems for a hybrid class of generalized contractive operators in the context of b-rectangular metric spaces. Examples justifying theorems and an open problem regarding to further generalizations for this type of operators are also given. Mathematics Subject Classification (2010): 47H10, 54H25.